Effect of selected dietary supplements on growth performance andproduction of pond reared deccan mahseer, Tor khudree (Sykes, 1839) - Basade, Yasmeen; Kohli, M P S; Ogale, S N (Indian Journal of Fisheries, 2016)
The effect of selected dietary supplements on the growth performance, survival, production, body composition and digestiveenzyme activityÂ in deccan mahseer reared under pond conditions was stuided. Cholicalciferol (CC), soylecithin (SL), thyroxine(TH) and betaine (BT) were added to the basal diet (BD) asÂ supplements at concentrations of 1800 IU kg-1, 3.5%, 0.05ppmand 0.5% respectively. After a rearing period of 180 days on experimental diets, soylecithin supplemented diet (SL) resultedin significantly higher (p<0.05) growth performance in terms of live weight, specific growth rate (SGR), fish biomass andfish production when compared with other diets. Feed conversion ratio (FCR) was significantly better (p<0.05) in the fishfed with the SL diet compared to fish fed on other diets. Carcass composition and energy content were significantly higher(p<0.05) in treated groups compared to the control group. Among all the treatments, body protein, lipid, ash and energycontents were highest in fish fed with the SL diet. Digestive enzyme activities in both the intestinal and liver tissues weresignificantly higher (p<0.05) in fish fed fortified diets compared to fish fed BD, with the highest values in fish fed SL diet.However, lipase activity, was not significantly different (p>0.05) from that of BD diet in the intestinal tissue of fish fed THdiet and in the liver of fish fed on CC, TH and BT diets. Soylecithin (3.5%) was found to be a better dietary supplementamong the treatments for rearingÂ deccan mahseer.